Analysis of secondary phases segregated and precipitated in SnO2-based varistors - Parra, Rodrigo (2004)
Transmission and scanning electron microscopy techniques were used to study the heterogeneities found in the microstructure of SnO2·Co3O4· Nb2O5·Fe2O3 and SnO2·ZnO·Nb2O5·Fe2O3 varistors. Second phases encountered both inside the grains and in grain boundary regions were identified using energy dispersive spectrometry and electron diffraction patterns. Through the electrical characterisation, the presence of iron oxide among the additives was determined to highlight the non-linear properties of the specimens. A discussion on the influence of second phases on the non-linear features of these systems is also addressed.